2001
DOI: 10.1007/s11741-996-0028-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of PWM modes on commutation torque ripples in sensorless brushless DC motor control system

Abstract: This paper introduces four PWM modes used in the sensorless brushless DC motor control system, analyzes their different influences on the commutation torque ripple in detail, and selects the best PWM mode in four given types to reduce commutation torque ripple of Brushless OC(BLDC) motors. Simulation and experimental results show that the selection is correct and practical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Therefore, it is widely applied in office automation, computer peripheral devices and instruments, as well as domestic electric appliances, etc. [1]. However, in a practical BLDCMbased drive, significant torque pulsations may arise due to the imperfect back-EMF waveform, commutation modes between phase windings, and cogging torque, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is widely applied in office automation, computer peripheral devices and instruments, as well as domestic electric appliances, etc. [1]. However, in a practical BLDCMbased drive, significant torque pulsations may arise due to the imperfect back-EMF waveform, commutation modes between phase windings, and cogging torque, etc.…”
Section: Introductionmentioning
confidence: 99%
“…[2]- [5]. Particularly, caused by the freewheeling of phase currents and limited DC-link bus voltages, the torque ripple during phase current commutation is usually considered as one of the main drawbacks of BLDCM drives, which varies with different PWM modes [6]- [8]. In addition, the non-commutation phase current as well as the output torque may also fluctuate significantly in the course of commutation period [9].…”
Section: Introductionmentioning
confidence: 99%
“…Various pulse‐width modulation (PWM) methods have been analysed which can eliminate the freewheeling action of diode to control electromagnetic torque. The study on the commutation torque ripple has been made under the conventional PWM techniques in [11, 12]. It is indicated that the torque ripple can be reduced to a lower level by using the PWM‐ON‐PWM strategy during commutation and non‐commutation intervals.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the absence of brushes leads to high reliability, low maintenance and high speed capability. Therefore, it is widely applied in office automation, computer peripheral devices, instruments, domestic electric appliances, etc [1]. However, in a practical BLDC drive, significant torque pulsations may arise due to the back-EMF waveform departing from the ideal, as well as commutation torque ripple, pulse width modulation (PWM) switching, and cogging [2] [3].…”
Section: Introductionmentioning
confidence: 99%